1999
DOI: 10.1097/00006454-199909000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal group B streptococcal disease in Finland: a ten-year nationwide study

Abstract: The clinical picture of GBS disease and serotype distribution are similar to what has been reported from other countries. Serotypes III and III/R dominated (47% of all infections), especially in late onset disease. On the basis of these results a GBS vaccine including at least the Ia, Ib, II and III components would provide coverage against 88% of GBS serotypes causing neonatal disease in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
50
2
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 34 publications
12
50
2
5
Order By: Relevance
“…Sequencing of the 790-bp PCR amplicon allows MS III to be subtyped on the basis of the sequence heterogeneity. Previous studies in the United States and several other countries have shown that serotypes Ia, Ib, II, III, and V are those most frequently isolated from normally sterile sites (9,11). Serotypes VI and VIII are the predominant serotypes isolated from patients in Japan (15) but are uncommon elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the 790-bp PCR amplicon allows MS III to be subtyped on the basis of the sequence heterogeneity. Previous studies in the United States and several other countries have shown that serotypes Ia, Ib, II, III, and V are those most frequently isolated from normally sterile sites (9,11). Serotypes VI and VIII are the predominant serotypes isolated from patients in Japan (15) but are uncommon elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Varios estudios han señalado, en las últimas dos décadas, un aumento en la incidencia del serotipo III en infecciones neonatales y maternas, constituyendo el serotipo más frecuentemente aislado en casos de sepsis neonatal y de meningitis 8,13,14,23 .…”
Section: Discussionunclassified
“…In Th-1 immune responses, IL-18 and IL-12 are important cytokines that may synergistically stimulate IFN-␥ production and enhance NK and T cell-mediated cytotoxicity (19). Recent studies implicate the interaction of these Th-1 cytokines in the development of autoimmune diseases and suggest that regulating their function may be therapeutically beneficial (20,21).Early-onset GBS infections in neonates often lead to sepsis and severe septic shock, with an approximate 5-15% mortality rate (22)(23)(24) …”
mentioning
confidence: 99%
“…Early-onset GBS infections in neonates often lead to sepsis and severe septic shock, with an approximate 5-15% mortality rate (22)(23)(24) …”
mentioning
confidence: 99%
See 1 more Smart Citation